2016
DOI: 10.1186/s12864-016-3103-6
|View full text |Cite
|
Sign up to set email alerts
|

Assisted transcriptome reconstruction and splicing orthology

Abstract: BackgroundTranscriptome reconstruction, defined as the identification of all protein isoforms that may be expressed by a gene, is a notably difficult computational task. With real data, the best methods based on RNA-seq data identify barely 21 % of the expressed transcripts. While waiting for algorithms and sequencing techniques to improve — as has been strongly suggested in the literature — it is important to evaluate assisted transcriptome prediction; this is the question of how alternative transcription in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…Values related to the alignments. While considering the retained alignments and applying a comparative genomics approach (Blanquart, et al 2016), we evaluated the presence or absence of the following functional sites observed in human exons: the motifs "AG" of the acceptor splice site (A value) and the "GT" of the donor splice site ( D value), the start codon "ATG" (T value) and the stop codons "TAA", "TAG" or "TGA" (P value). Occurrences of putative orthologous stop codons were also assessed to appear in the same frame as observed for the human stop codon.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Values related to the alignments. While considering the retained alignments and applying a comparative genomics approach (Blanquart, et al 2016), we evaluated the presence or absence of the following functional sites observed in human exons: the motifs "AG" of the acceptor splice site (A value) and the "GT" of the donor splice site ( D value), the start codon "ATG" (T value) and the stop codons "TAA", "TAG" or "TGA" (P value). Occurrences of putative orthologous stop codons were also assessed to appear in the same frame as observed for the human stop codon.…”
Section: Methodsmentioning
confidence: 99%
“…In 2016, GenBank and Refseq cDNA databases referenced 152,726 and 110,720 human mRNAs, respectively, with an average number of mRNA isoforms per gene ranging from 4 to 8 in humans (Pan, et al 2008). Moreover, in the same year, another study reported that the number of orthologous coding isoforms discovered in humans and mice has grown constantly over the past ten years (Blanquart, et al 2016). However, the coverage bias at the 5'-and 3'-ends of mRNA sequencing results in underrepresentation of mRNA extremities (Kukurba and Montgomery 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, in Figure 9, the spliced alignment of g[c 1 ] against g is A = { (1,4,9,12), (5,16,18,29), (17,24,49,56)} (see Figure 10 for more general examples of spliced alignments with conserved and deleted blocks ). A spliced alignment A induces a set of putative gene intron segments.…”
Section: For Any Two Blocksmentioning
confidence: 99%
“…Identifying orthologous isoforms at transcript level is a prerequisite to describing evolutionary relationships between genes in terms of splicing structure and sets of splice variants [5,17]. Here, we focus on the spliced alignment of full CDS against gene sequences within a gene family, which allows to identify splicing orthologous CDS with similar sequences and splicing structures from genes that have evolved from a common ancestral gene [26,1]. Splicing orthologs are supposed to have retained the same function in the course of evolution.…”
Section: Introductionmentioning
confidence: 99%